Моніторинг факторів впливу зовнішнього середовища на функціонування роздрібної мережі - Данкеєва, Оксана Миколаївна (My University, 2022)
У статті здійснено моніторинг факторів впливу зовнішнього середовища на функціонування роздрібної мережі з використанням PESTLE-аналізу. Наведено характеристику діяльності та основні напрямки розвитку національної роздрібної мережі VARUS. Визначено перелік факторів впливу зовнішнього середовища та їх складових. Сформульовано межі ймовірнісості зміни чи настання фактору. Проведено експертне оцінювання вірогідності змін факторів зовнішнього середовища та їх ймовірності настання. Здійснено оцінку сили впливу кожного фактору зовнішнього середовища та його складових на функціонування роздрібної мережі, а також ймовірності їх настання. Наведено та обґрунтовано результати оцінки сили впливу факторів зовнішнього середовища та їх складових на функціонування роздрібної мережі. Зазначено перспективи подальшої реалізації намічених напрямів розвитку роздрібної мережі з урахуванням впливу факторів зовнішнього середовища. The external environment of retail networks is characterized by variability of consumer demand, complexity, dynamism, intensity of influence. Also, the processes that take place in the external environment contain many contradictions, as a result, it is necessary to constantly monitor, analyze and systematically study the factors of their impact on the functioning of retail networks in the dynamic nature of change. The aim of the article is to monitor and determine the strength of environmental factors and the probability of their occurrence on the operation of the retail network, using PESTLE-analysis. The impact of environmental factors on the functioning of retail enterprises was monitored on the example of the VARUS retail network. VARUS is a national supermarket chain represented on the Ukrainian grocery retail market by Omega in 25 predominantly large cities. As the VARUS retail network plans to expand its number of stores in the new, saturated with competitors retail market in Kyiv region, as well as to introduce new areas of activity – PESTLE-analysis will provide the necessary data for the planned areas of network development, assess potential risks and measure strength. the impact of each of the environmental factors and the probability of their occurrence. The analysis showed that almost all the studied environmental factors have a moderate negative impact on the functioning of the retail network VARUS with a probability of change of factors in the range of 60-80%. The components of the technological factor have a positive effect, which indicates the readiness of the network to introduce the latest technologies in trade. Monitoring the strength of the influence of factors and assessing the probability of their change on the functioning of the retail network VARUS in the future shows that the influence of environmental factors – the result of the interaction of many components, each of which is unique in a particular situation. The need for continuous monitoring of the strength of the impact of environmental factors and the probability of their occurrence is necessary in order to predict the nature and extent of their impact, to capture tendencies, and to implement the necessary measures in a timely manner.
Keywords: кафедра маркетингу; фактори зовнішнього середовища та їх складові; сила впливу фактору; PESTLE-аналіз; роздрібна мережа; експертні оцінки; негативний вплив; environmental factors and their components; strength of factor influence; PESTLE-analys; retail network; expert assessments; negative impact